2018
DOI: 10.1186/s40942-018-0135-x
|View full text |Cite
|
Sign up to set email alerts
|

Retina and glaucoma: surgical complications

Abstract: BackgroundThe close structural and microcirculatory co-relation between anterior and posterior segments of eye make them very vulnerable to complications when one of them is affected surgically. With the advent of anti-fibrotic agents in the management of glaucoma, the rates of vitreoretinal complications have become more frequent. Main bodyCommon retinal complications after glaucoma surgeries include choroidal detachment; ocular decompression retinopathy; haemorrhagic choroidal detachment; hypotony maculopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 106 publications
2
21
0
7
Order By: Relevance
“…The IOP scores at the beginning and end of the follow-up period were not significantly different. The findings from the present study are supported by several studies that have shown that endotamponade with silicone oil predisposed patients undergoing PPV to developing secondary glaucoma [17,27,28].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The IOP scores at the beginning and end of the follow-up period were not significantly different. The findings from the present study are supported by several studies that have shown that endotamponade with silicone oil predisposed patients undergoing PPV to developing secondary glaucoma [17,27,28].…”
Section: Discussionsupporting
confidence: 89%
“…Although silicone oil can provide a long duration of tamponade and enhances efficacy in difficult cases, applying the oil frequently leads to complications, such as keratopathy, glaucoma, or cataract [13][14][15][16]. Glaucoma is one of the most common complications following the use of silicone oil endotamponade, which occurs due to several pathophysiological mechanisms, including the pupillary block, inflammatory angle closure by synechiae, rubeosis of the iris, and migration of emulsified and non-emulsified silicone oil to the anterior chamber [14][15][16][17][18]. Infiltration and occlusion of the trabecular reticulum are believed to drive the pathophysiology of silicone-induced secondary open-angle glaucoma (OAG) [14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, vitrectomy for RD repair still has unwanted side effects due to the use of tamponades. Intraocular silicon oil and/or expansive gases may produce, even when they are no longer inside the eye, visual impairment, cataracts and glaucoma [4,5]. As the efficacy of the current RD surgery technique (measured by the binary endpoint of "attached/not attached") is well past 90%, retinal surgeons undertake the described side effects as part of the technique.…”
Section: Discussionmentioning
confidence: 99%
“…Laser retinopexy is the preferred technique, nevertheless its effect is not immediate [3], thus necessitates the use of a temporal endotamponade to maintain both tissues in apposition. Long-acting gases and silicone oil are widely used to accomplish this purpose; nonetheless, they are not exempt from side effects, namely, visual acuity impairment during tamponade, cataracts [4] and glaucoma [5] among others. Furthermore, due to their physical properties, they are prone to fail in the context of inferior retinal…”
Section: Introductionmentioning
confidence: 99%
“…There are several mechanisms proposed for early rise in IOP like increased inflammation, hyphemia, silicone oil overfill, choroidal or supraciliary effusion, pupillary block, steroid-induced elevated IOP, and worsening of preexisting glaucoma. [ 1 2 3 ] Emulsified silicone oil, steroid response, worsening of primary open-angle glaucoma, and neovascular glaucoma are some of the mechanisms for late postoperative elevation in IOP. [ 2 4 5 ] Understanding the underlying mechanism is critical for appropriate treatment.…”
mentioning
confidence: 99%